1979
DOI: 10.1159/000117687
|View full text |Cite
|
Sign up to set email alerts
|

L-5-HTP Treatment and Serum 5-HT Level after L-5-HTP Loading on Depressed Patients

Abstract: Based on 5-HT hypothesis, L-5-HTP (150 or 300 mg/day) was given orally to 18 depressed patients. The global estimates were 2 very much improved; 8 much improved; 3 minimally improved, and 5 unchanged. The action of L-5-HTP was usually rapid. The elevation of the serum 5-HT level 1 week after L-5-HTP administration was relatively lower in the 5-HTP nonresponder group, compared with the responders. The chronological change of the serum 5-HT level in depressed patients after an oral loading dose of 3 mg/kg of L-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The therapeutic efficacy in our study did not prove to be dose-dependent, which supports the studies of Angst [15], Van Hiele [13], Kaneko et al [16], Matussek et al [17] and Van Praag [ 18], An average daily dose of 200 mg L-5-HTP seems to be effective in most patients. An interesting finding is the observation of Van Hiele [13] that some of his patients responded rather to a low than to a large dose of L-5-HTP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The therapeutic efficacy in our study did not prove to be dose-dependent, which supports the studies of Angst [15], Van Hiele [13], Kaneko et al [16], Matussek et al [17] and Van Praag [ 18], An average daily dose of 200 mg L-5-HTP seems to be effective in most patients. An interesting finding is the observation of Van Hiele [13] that some of his patients responded rather to a low than to a large dose of L-5-HTP.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with Angst et al [15], Van Hiele [13], Kaneko et al [16], Matussek et al [17] and Van Praag [18] the treatment response was not found to be dosedependent, and there was no evidence that the adminis tration of benserazide intensified the efficacy of L-5-HTP. A review of the literature on this subject revealed that T-5-HTP given alone was more effective (249 out of 389 patients, 64%) than the combination of L-5-HTP with a peripheral decarboxylase inhibitor (93 out of 176 patients, 52.9%).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, 5-HTP was administered to hundreds of patients at doses ranging from 50 to 600 mg per day (in some cases up to 3250 mg per day) for the treatment of various types of depression, fibomyalgia, obesity, chronic headaches (migraines) and insomnia (Sano, 1971a(Sano, ,b, 1972Wyatt et al, 1971;Fujiwara and Otsuki, 1973;Matussek et al, 1974;Takahashi et al, 1975;Angst et al, 1977;Nakajima et al, 1978;van Hiele, 1980;Kaneko et al, 1979;van Praag et al, 1972van Praag et al, , 1974Brodie et al, 1973;Barlet and Pailard, 1973;Guilleminault et al, 1973;Lopez-Ibor Alino et al, 1976;Soulairac and Lambinet, 1977;Mendlewicz and Youdim, 1980;Boiardi et al,1981;Bono et al, 1984;Longo et al, 1984;De Benedittis and Massei, 1985;Kahn and Westenberg, 1985;Titus et al, 1986;Byerley et al, 1987;De Giorgis et al, 1987;Conte, 1988;Zmilacher et al, 1988;Westenberg and den Boer, 1989;Caruso et al, 1990;Den Boer and Westenberg, 1990;Agren et al, 1991;Maissen and Ludin, 1991;Poldinger et al, 1991;Cangiano et al, 1992;Puttini and Caruso, 1992;Nicolodi and Sicuteri, 1996). In all these studies, no adverse reactions related to EMS were noted, nor there were any other significant ...…”
Section: Clinical Studies With 5-hydroxy-l-tryptophanmentioning
confidence: 99%
“…The antidepressive action of 5-HTP has revealed itself in a number of open [74][75][76][77][78] and controlled [79][80][81] studies, as well as in double-blind comparisons with standard tri cyclic antidepressants [70][71][72], with about two thirds of the patients showing a good to very good improvement. Although some of these studies have been questioned on meth odological grounds [82], and a few clinical trials failed to reveal a clearcut antidepres sive effect of 5-HTP [83][84][85][86], the overall evi dence is in favor of this serotonin precursor.…”
Section: Antidepressive Action O F 5-htpmentioning
confidence: 99%